Anti-aging asphalt and production process thereof
By adding waste rubber, cycloane oil, SBS and other raw materials to the asphalt, and preparing composite anti-aging agents, the synergistic effect of carrier microspheres and network wrapping layer is used to solve the problem of insufficient anti-aging performance of existing asphalt, which is significantly extended The service life of asphalt.
Patent Information
- Application Number
- CN202411591542.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
The anti-aging performance of existing modified asphalt is insufficient, resulting in aging under environmental factors such as heat, air, and sunlight, degradation of performance and shortening of service life.
90 to 100 parts of matrix asphalt, 15 to 25 parts of waste rubber, 5 to 8 parts of cycloane oil, 1.0 to 1.5 parts of thiuram disulfide, 10 to 15 parts of styrene-butadiene block copolymer SBS, 0.5 The formula of ~0.8 parts of zinc acetylacetonate and 2.5 to 3.5 parts of composite anti-aging agent is improved by the preparation method of composite anti-aging agent, including the preparation of carrier microspheres and the formation of network wrapping layers.
It significantly improves the anti-aging performance of asphalt, extends its service life, and ensures its quality and quality.
Smart Images

Figure BDA0005125719970000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to an anti-aging asphalt and a production process thereof. Background Art
[0002] Asphalt is a dark brown complex mixture of hydrocarbons of different molecular weights and their non-metallic derivatives. It is a waterproof, moisture-proof and anti-corrosive organic gelling material, mostly in the form of asphalt or tar. The surface of asphalt is black and soluble in carbon disulfide. It is mainly divided into three types: coal tar asphalt, petroleum asphalt and natural asphalt. It is mainly used in coatings, plastics, rubber and other industries as well as pavement and other fields.
[0003] The patent document with application number "201310603066.5" discloses a high storage stability rubber powder modified asphalt and its preparation method, which is composed of base asphalt, rubber powder, a compatibilizer and a stabilizer. The weight of the rubber powder is 15% to 30% of the weight of the base asphalt, the weight of the compatibilizer is 2.0% to 5.0% of the weight of the base asphalt, and the weight of the stabilizer is 1.2% to 2.5% of the weight of the base asphalt.
[0004] Although the rubber powder modified asphalt prepared according to the above patent document has excellent storage stability and the preparation process is relatively simple and easy, the anti-aging performance of the modified asphalt prepared therefrom is relatively insufficient. When asphalt is exposed to environmental factors such as heat, air, and sunlight, a series of volatilization, oxidation, and polymerization phenomena occur, and even the internal structure of the asphalt changes, and the properties and structure change at the same time, leading to a process of deterioration of road performance. Its macroscopic manifestation is an increase in softening point, a decrease in needle penetration, and a decrease in ductility. The deterioration of these physical indicators is called aging. Not only will the mechanical properties of the aged asphalt decline, but its service life will also be shortened, which affects its quality or quality while also shortening its service life. Therefore, the present invention provides an anti-aging asphalt and a production process thereof to solve the above-mentioned technical problems! Summary of the invention
[0005] The purpose of the present invention is to provide an anti-aging asphalt and a production process thereof. The produced asphalt has excellent anti-aging performance, which prolongs its service life to a certain extent while also ensuring its quality.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] An anti-aging asphalt is composed of the following raw materials in parts by weight: 90-100 parts of base asphalt, 15-25 parts of waste rubber, 5-8 parts of cyclohexane oil, 1.0-1.5 parts of thiuram disulfide, 10-15 parts of styrene-butadiene block copolymer SBS, 0.5-0.8 parts of zinc acetylacetonate and 2.5-3.5 parts of a composite anti-aging agent.
[0008] Furthermore, the waste rubber is selected from any one of waste tire rubber and waste sole rubber, and the particle size of the waste rubber is 40 to 70 meshes.
[0009] Furthermore, the base asphalt is selected from any one of petroleum asphalt, natural asphalt and coal asphalt.
[0010] Furthermore, the preparation method of the composite antioxidant comprises the following steps:
[0011] Step 1, the pre-treated carrier microspheres are uniformly dispersed in DMF at a solid-liquid ratio of 10 to 30 g / L, nitrogen is introduced, and 2 to 4% of diaminoethane and 15 to 25% of 2,2'-4-trihydroxybenzophenone are added at a temperature of 50 to 70° C. while stirring; after the reaction is kept warm for 5 to 10 hours, the reaction product is centrifuged, the filter cake is washed with DMF 3 to 4 times and then vacuum dried at a temperature of 50 to 60° C. for 20 to 30 hours, and the obtained is recorded as modified carrier microspheres;
[0012] Step 2, 4-octyl-N-(4-octylphenyl)aniline and γ-glycidyloxypropyltrimethoxysilane are mixed uniformly at a mass ratio of 1 to 1.5:1, and then the mixture is kept warm at a temperature of 90 to 110°C for reaction for 3 to 6 hours. After the reaction is completed, the resulting component is naturally cooled to 50 to 65°C, and then an ethanol aqueous solution with a mass of 2 to 3 times that of 4-octyl-N-(4-octylphenyl)aniline and a volume concentration of 80 to 90% is added thereto, and the mixture is mechanically stirred for 50 to 80 minutes to obtain a mixed component;
[0013] Step 3: Add the modified carrier microspheres into the mixed components at a solid-liquid ratio of 5 to 10 g / L, then add 2-(2'-hydroxy-5'-methylphenyl)benzotriazole in an amount of 2 to 3% by mass of the mixed components, and heat to 55 to 65° C. under nitrogen protection. After stirring and reacting for 5 to 8 hours, separate the solid and liquid of the reaction product, and wash and vacuum dry the obtained filter cake to obtain a composite antioxidant.
[0014] Furthermore, the preparation method of the pre-treated carrier microspheres is: the carrier microspheres are put into toluene at a solid-liquid ratio of 0.03 to 0.08 g / mL, and then silane coupling agent KH-560 is added in an amount 0.3 to 0.5 times the mass of the carrier microspheres, and after ultrasonic dispersion, the mixture is stirred and kept warm at 80 to 90° C. for 5 to 8 hours; after the reaction is completed, the resulting components are centrifuged, washed and dried in turn, and the final product is the pre-treated carrier microspheres.
[0015] Furthermore, the preparation method of the carrier microspheres includes the following steps: ultrasonically mixing glacial acetic acid and ethylene glycol at a volume ratio of 1:20 to 30, adding a cerium nitrate aqueous solution thereto, mixing and stirring evenly, and heat-retaining the resulting mixture at a temperature of 150 to 180° C. for 3 to 5 hours; after the reaction is completed, centrifuging, washing, drying and high-temperature calcining the resulting components in turn, and the final product is the carrier microspheres.
[0016] Furthermore, the concentration of the cerium nitrate aqueous solution is 0.5-1 mol / L, and the concentration of cerium nitrate in the mixed solution is 0.03-0.05 g / mL.
[0017] Furthermore, the calcination temperature during the high-temperature calcination treatment is set to 450-480° C., and the calcination time is set to 3-5 hours.
[0018] A production process for anti-aging asphalt comprises the following steps: accurately weighing various raw materials according to the formula amount, adding cyclohexane oil and styrene-butadiene block copolymer SBS into molten matrix asphalt, adding thiuram disulfide and zinc acetylacetonate after heat preservation and stirring evenly, and then heat preservation and stirring at a rate of 600-1000r / min for 60-90min; adding the remaining raw materials after stirring is completed, and then heat preservation and stirring evenly to obtain the anti-aging asphalt.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The present invention uses glacial acetic acid and cerium nitrate as raw materials to prepare carrier microspheres with a porous spherical structure. The carrier microspheres are put into toluene and a silane coupling agent KH-560 is added. After ultrasonic dispersion, the pre-treated carrier microspheres are stirred and reacted to obtain the pre-treated carrier microspheres. Then, the pre-treated carrier microspheres are evenly dispersed in DMF, and diaminoethane and 2,2'-4-trihydroxybenzophenone are added while stirring under the protection of a nitrogen atmosphere. The pre-treated carrier microspheres are reacted chemically under the action of diaminoethane. Finally, 2,2'-4-trihydroxybenzophenone is connected to the relevant active groups on the surface of the pre-treated carrier microspheres through chemical bonds, so that they are effectively loaded on the surface of the pre-treated carrier microspheres and the inner wall of their porous structure, thereby obtaining modified carrier microspheres. The prepared modified carrier microspheres have excellent anti-aging properties under the synergistic cooperation of the carrier microspheres and the dense 2,2'-4-trihydroxybenzophenone network wrapping layer on their surfaces.
[0021] 2. Mix 4-octyl-N-(4-octylphenyl)aniline and γ-glycidyloxypropyltrimethoxysilane and keep them warm for reaction. After the reaction is completed, add ethanol aqueous solution and stir mechanically to obtain a mixed component. Then put the modified carrier microspheres into the mixed component and add 2-(2'-hydroxy-5'-methylphenyl)benzotriazole. Keep them warm and stir them under the protection of nitrogen atmosphere. During the reaction, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole can be evenly dispersed and adsorbed on the surface of the carrier microspheres and inside their porous structure. γ-glycidyloxypropyltrimethoxysilane reacts with the relevant active groups on the modified carrier microspheres, and then 4-octyl-N-(4-octylphenyl)aniline is "grafted" onto the modified carrier microspheres through chemical bonds under the mediation of γ-glycidyloxypropyltrimethoxysilane, and finally a dense 4-octyl-N-(4-octylphenyl)aniline network coating layer is formed on the surface of the modified carrier microspheres. The 2,2'-4-trihydroxybenzophenone network coating layer and the 4-octyl-N-(4-octylphenyl)aniline network coating layer can play a good "confinement" role for 2-(2'-hydroxy-5'-methylphenyl)benzotriazole retained on the surface and inside of the modified carrier microspheres, reducing the probability of its migration. Finally, under the synergistic effect of carrier microspheres, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, and two layers of network wrapping layers, the prepared composite antioxidant has excellent anti-aging properties. Its use as a raw material for producing asphalt can significantly improve its anti-aging properties, extend its service life to a certain extent, and also ensure its quality. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1
[0024] An anti-aging asphalt is composed of the following raw materials in parts by weight: 90 parts of petroleum asphalt, 15 parts of waste tire rubber with a particle size of 40 meshes, 5 parts of naphthenic oil, 1.0 part of thiuram disulfide, 10 parts of styrene-butadiene block copolymer SBS, 0.5 parts of zinc acetylacetonate and 2.5 parts of a composite anti-aging agent.
[0025] The preparation method of the composite antioxidant comprises the following steps:
[0026] Step 1, the pre-treated carrier microspheres are uniformly dispersed in DMF at a solid-liquid ratio of 10g / L, nitrogen is introduced, and 2% of diaminoethane and 15% of 2,2'-4-trihydroxybenzophenone are added at a temperature of 50°C while stirring; after the reaction is kept warm for 5 hours, the reaction product is centrifuged, the filter cake is washed 3 times with DMF and then vacuum dried at a temperature of 50°C for 20 hours, and the obtained is recorded as modified carrier microspheres;
[0027] Step 2, 4-octyl-N-(4-octylphenyl)aniline and γ-glycidyloxypropyltrimethoxysilane are mixed uniformly and then kept at 90° C. for reaction for 3 hours. After the reaction is completed, the resulting component is naturally cooled to 50° C., and then an ethanol aqueous solution with a mass of 2 times that of 4-octyl-N-(4-octylphenyl)aniline and a volume concentration of 80% is added thereto, and mechanical stirring is performed for 50 minutes to obtain a mixed component;
[0028] Step 3: Add the modified carrier microspheres into the mixed components at a solid-liquid ratio of 5 g / L, then add 2-(2'-hydroxy-5'-methylphenyl)benzotriazole (2% by mass of the mixed components), and heat to 55°C under nitrogen protection. After stirring and reacting for 5 hours, the reaction product is separated into solid and liquid. The filter cake is washed and vacuum dried in turn to obtain a composite antioxidant.
[0029] The preparation method of the pre-treated carrier microspheres is as follows: the carrier microspheres are put into toluene at a solid-liquid ratio of 0.03 g / mL, and then a silane coupling agent KH-560 is added with a mass 0.3 times that of the carrier microspheres, and after ultrasonic dispersion, the mixture is stirred and reacted at 80° C. for 5 hours; after the reaction is completed, the obtained product components are centrifuged, washed and dried in sequence, and the final product is the pre-treated carrier microspheres.
[0030] The preparation method of the carrier microspheres comprises the following steps: after uniformly mixing glacial acetic acid and ethylene glycol by ultrasonic mixing at a volume ratio of 1:20, adding a cerium nitrate aqueous solution thereto, mixing and stirring evenly, and then heat-insulating the obtained mixed solution at a temperature of 150°C for reaction for 3 hours; after the reaction is completed, centrifuging, washing, drying and high-temperature calcining the obtained product components in sequence, and finally obtaining the carrier microspheres; wherein the concentration of the cerium nitrate aqueous solution is 0.5 mol / L, and the concentration of cerium nitrate in the mixed solution is 0.03 g / mL; the calcination temperature during the high-temperature calcination treatment is set to 450°C, and the calcination time is set to 3 hours.
[0031] A production process for anti-aging asphalt comprises the following steps: accurately weighing various raw materials according to the formula amount, adding cyclohexane oil and styrene-butadiene block copolymer SBS into molten matrix asphalt, adding thiuram disulfide and zinc acetylacetonate after heat preservation and stirring evenly, and then heat preservation and stirring at a rate of 600r / min for 60min; adding the remaining raw materials after stirring is completed, and then heat preservation and stirring evenly to obtain the anti-aging asphalt.
[0032] Example 2
[0033] The production process of an anti-aging asphalt provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the raw materials used and the preparation method of the composite antioxidant are not completely the same. The specific composition of the raw materials used in this embodiment and the preparation method of the composite antioxidant are as follows:
[0034] An anti-aging asphalt is composed of the following raw materials in parts by weight: 95 parts of petroleum asphalt, 20 parts of waste tire rubber with a particle size of 40 meshes, 6 parts of cyclohexane oil, 1.2 parts of thiuram disulfide, 12 parts of styrene-butadiene block copolymer SBS, 0.5 parts of zinc acetylacetonate and 3.0 parts of a composite anti-aging agent.
[0035] The preparation method of the composite antioxidant comprises the following steps:
[0036] Step 1, the pre-treated carrier microspheres are uniformly dispersed in DMF at a solid-liquid ratio of 20g / L, nitrogen is introduced, and 3% of diaminoethane and 20% of 2,2'-4-trihydroxybenzophenone are added at a temperature of 60°C while stirring; after the reaction is kept warm for 8 hours, the reaction product is centrifuged, the filter cake is washed 3 times with DMF and then vacuum dried at a temperature of 55°C for 25 hours, and the obtained is recorded as modified carrier microspheres;
[0037] Step 2, 4-octyl-N-(4-octylphenyl)aniline and γ-glycidyloxypropyltrimethoxysilane are mixed evenly at a mass ratio of 1.2:1, and the mixture is kept warm for reaction at 100°C for 5 hours. After the reaction is completed, the resulting component is naturally cooled to 60°C, and then an ethanol aqueous solution with a mass of 3 times that of 4-octyl-N-(4-octylphenyl)aniline and a volume concentration of 85% is added thereto, and the mixture is mechanically stirred for 60 minutes to obtain a mixed component;
[0038] Step 3: Add the modified carrier microspheres into the mixed components at a solid-liquid ratio of 8 g / L, then add 2-(2'-hydroxy-5'-methylphenyl)benzotriazole in an amount of 2.5% by mass of the mixed components, and heat to 60°C under nitrogen protection. After stirring and reacting for 6 hours, separate the solid and liquid of the reaction product, and wash and vacuum dry the obtained filter cake to obtain a composite antioxidant.
[0039] The preparation method of the pre-treated carrier microspheres is as follows: the carrier microspheres are put into toluene at a solid-liquid ratio of 0.05 g / mL, and then a silane coupling agent KH-560 is added in an amount 0.4 times the mass of the carrier microspheres, and after ultrasonic dispersion, the mixture is stirred and reacted at 85° C. for 6 hours; after the reaction is completed, the obtained product components are centrifuged, washed and dried in sequence, and the final product is the pre-treated carrier microspheres.
[0040] The preparation method of the carrier microspheres comprises the following steps: after uniformly mixing glacial acetic acid and ethylene glycol by ultrasonic mixing at a volume ratio of 1:25, adding a cerium nitrate aqueous solution thereto, mixing and stirring evenly, and then heat-insulating the obtained mixed solution at a temperature of 160° C. for 4 hours; after the reaction is completed, centrifuging, washing, drying and high-temperature calcining the obtained product components in sequence, and finally obtaining the carrier microspheres; wherein the concentration of the cerium nitrate aqueous solution is 0.8 mol / L, and the concentration of cerium nitrate in the mixed solution is 0.04 g / mL; the calcination temperature during the high-temperature calcination treatment is set to 460° C., and the calcination time is set to 4 hours.
[0041] Example 3
[0042] The production process of an anti-aging asphalt provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the raw materials used and the preparation method of the composite antioxidant are not completely the same. The specific composition of the raw materials used in this embodiment and the preparation method of the composite antioxidant are as follows:
[0043] An anti-aging asphalt is composed of the following raw materials in parts by weight: 100 parts of petroleum asphalt, 25 parts of waste tire rubber with a particle size of 40 meshes, 8 parts of naphthenic oil, 1.5 parts of thiuram disulfide, 15 parts of styrene-butadiene block copolymer SBS, 0.8 parts of zinc acetylacetonate and 3.5 parts of a composite anti-aging agent.
[0044] The preparation method of the composite antioxidant comprises the following steps:
[0045] Step 1, the pre-treated carrier microspheres are uniformly dispersed in DMF at a solid-liquid ratio of 30g / L, nitrogen is introduced, and 4% of diaminoethane and 25% of 2,2'-4-trihydroxybenzophenone are added at a temperature of 70°C while stirring; after the reaction is kept warm for 10 hours, the reaction product is centrifuged, the filter cake is washed 4 times with DMF and then vacuum dried at a temperature of 60°C for 30 hours, and the obtained is recorded as modified carrier microspheres;
[0046] Step 2, 4-octyl-N-(4-octylphenyl)aniline and γ-glycidyloxypropyltrimethoxysilane are mixed evenly at a mass ratio of 1.5:1, and then the mixture is kept warm for reaction at a temperature of 110°C for 6 hours. After the reaction is completed, the resulting component is naturally cooled to 65°C, and then an ethanol aqueous solution with a mass of 3 times that of 4-octyl-N-(4-octylphenyl)aniline and a volume concentration of 90% is added thereto, and the mixture is mechanically stirred for 80 minutes to obtain a mixed component;
[0047] Step 3: Add the modified carrier microspheres into the mixed components at a solid-liquid ratio of 10 g / L, then add 2-(2'-hydroxy-5'-methylphenyl)benzotriazole (3% by mass of the mixed components), and heat to 65°C under nitrogen protection. After stirring and reacting for 8 hours, separate the solid and liquid of the reaction product, and wash and vacuum dry the obtained filter cake to obtain a composite antioxidant.
[0048] The preparation method of the pre-treated carrier microspheres is as follows: the carrier microspheres are put into toluene at a solid-liquid ratio of 0.08 g / mL, and then a silane coupling agent KH-560 is added with a mass 0.5 times that of the carrier microspheres, and after ultrasonic dispersion, the mixture is stirred and reacted at 90° C. for 8 hours; after the reaction is completed, the obtained product components are centrifuged, washed and dried in sequence, and the final product is the pre-treated carrier microspheres.
[0049] The preparation method of the carrier microspheres comprises the following steps: after ultrasonically mixing glacial acetic acid and ethylene glycol at a volume ratio of 1:30, adding a cerium nitrate aqueous solution thereto, stirring the mixture evenly, and then heat-retaining the resulting mixture at a temperature of 180°C for 5 hours; after the reaction is completed, centrifuging, washing, drying and high-temperature calcining the resulting components in sequence, and finally obtaining carrier microspheres; wherein the concentration of the cerium nitrate aqueous solution is 1 mol / L, and the concentration of cerium nitrate in the mixture is 0.05 g / mL; the calcination temperature during the high-temperature calcination treatment is set to 480°C, and the calcination time is set to 5 hours.
[0050] Comparative Example 1: The main difference between this example and Example 1 is that an equal amount of carrier microspheres is used in this example to replace the composite antioxidant.
[0051] Comparative Example 2: The main difference between this example and Example 1 is that in this example, an equal amount of modified carrier microspheres are used instead of the composite antioxidant.
[0052] Comparative Example 3: The main difference between this example and Example 1 is that 2-(2'-hydroxy-5'-methylphenyl)benzotriazole is not used in the preparation of the composite antioxidant in this example.
[0053] Performance Testing
[0054] The relevant properties of the anti-aging asphalt samples produced in Examples 1 to 3 and Comparative Examples 1 to 3 were tested respectively, and the obtained test data were recorded in the following table:
[0055]
[0056] Note: The UV aging test conditions corresponding to the penetration ratio and softening point difference in the table are: UV intensity is 1200μw / cm 2 , the aging temperature is 60℃ and the aging time is 6 days.
[0057] By comparing and analyzing the relevant data in the table, it can be seen that the asphalt produced by the present invention has excellent anti-aging performance, which prolongs its service life to a certain extent while also ensuring its quality. This shows that the anti-aging asphalt and its production process provided by the present invention have a broader market prospect and are more suitable for promotion.
[0058] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0059] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. An anti-aging asphalt, characterized in that: The invention is composed of the following raw materials in parts by weight: 90-100 parts of base asphalt, 15-25 parts of waste rubber, 5-8 parts of cyclohexane oil, 1.0-1.5 parts of thiuram disulfide, 10-15 parts of styrene-butadiene block copolymer SBS, 0.5-0.8 parts of zinc acetylacetonate and 2.5-3.5 parts of composite anti-aging agent.
2. The anti-aging asphalt according to claim 1, characterized in that: The waste rubber is selected from any one of waste tire rubber and waste sole rubber, and the particle size of the waste rubber is 40-70 meshes.
3. The anti-aging asphalt according to claim 1, characterized in that: The matrix asphalt is selected from any one of petroleum asphalt, natural asphalt and coal asphalt.
4. The anti-aging asphalt according to claim 1, characterized in that: The preparation method of the composite antioxidant comprises the following steps: Step 1, the pre-treated carrier microspheres are uniformly dispersed in DMF at a solid-liquid ratio of 10 to 30 g / L, nitrogen is introduced, and 2 to 4% of diaminoethane and 15 to 25% of 2,2'-4-trihydroxybenzophenone are added at a temperature of 50 to 70° C. while stirring; after the reaction is kept warm for 5 to 10 hours, the reaction product is centrifuged, the filter cake is washed with DMF 3 to 4 times and then vacuum dried at a temperature of 50 to 60° C. for 20 to 30 hours, and the obtained is recorded as modified carrier microspheres; Step 2, 4-octyl-N-(4-octylphenyl)aniline and γ-glycidyloxypropyltrimethoxysilane are mixed uniformly at a mass ratio of 1 to 1.5:1, and then the mixture is kept warm at a temperature of 90 to 110°C for reaction for 3 to 6 hours. After the reaction is completed, the resulting component is naturally cooled to 50 to 65°C, and then an ethanol aqueous solution with a mass of 2 to 3 times that of 4-octyl-N-(4-octylphenyl)aniline and a volume concentration of 80 to 90% is added thereto, and the mixture is mechanically stirred for 50 to 80 minutes to obtain a mixed component; Step 3: Add the modified carrier microspheres into the mixed components at a solid-liquid ratio of 5 to 10 g / L, then add 2-(2'-hydroxy-5'-methylphenyl)benzotriazole in an amount of 2 to 3% by mass of the mixed components, and heat to 55 to 65° C. under nitrogen protection. After stirring and reacting for 5 to 8 hours, separate the solid and liquid of the reaction product, and wash and vacuum dry the obtained filter cake to obtain a composite antioxidant.
5. The anti-aging asphalt according to claim 4, characterized in that: The preparation method of the pre-treated carrier microspheres is as follows: the carrier microspheres are put into toluene at a solid-liquid ratio of 0.03 to 0.08 g / mL, and then a silane coupling agent KH-560 is added in an amount of 0.3 to 0.5 times the mass of the carrier microspheres, and after ultrasonic dispersion, the mixture is stirred and reacted at 80 to 90° C. for 5 to 8 hours; after the reaction is completed, the obtained product components are centrifuged, washed and dried in sequence, and the final product is the pre-treated carrier microspheres.
6. The anti-aging asphalt according to claim 5, characterized in that: Preparation method of the carrier microspheres The method comprises the following steps: uniformly mixing glacial acetic acid and ethylene glycol by ultrasonic mixing at a volume ratio of 1:20-30, adding cerium nitrate aqueous solution thereto, uniformly mixing and stirring, and heat-insulating the obtained mixed solution at a temperature of 150-180 DEG C for reaction for 3-5 hours; after the reaction is completed, centrifugally separating, washing, drying and high-temperature calcining the obtained product components in sequence, and finally obtaining carrier microspheres.
7. The anti-aging asphalt according to claim 6, characterized in that: The concentration of the cerium nitrate aqueous solution is 0.5-1 mol / L, and the concentration of the cerium nitrate in the mixed solution is 0.03-0.05 g / mL.
8. The anti-aging asphalt according to claim 6, characterized in that: The calcination temperature during the high-temperature calcination treatment is set to 450 to 480° C., and the calcination time is set to 3 to 5 hours.
9. A production process for anti-aging asphalt according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: accurately weighing each raw material according to the formula amount, adding cycloparaffin oil and styrene-butadiene block copolymer SBS into molten matrix asphalt, adding thiuram disulfide and zinc acetylacetonate after heat preservation and stirring evenly, and then heat preservation and stirring at a rate of 600-1000r / min for 60-90min; adding the remaining raw materials after stirring is completed, and then heat preservation and stirring evenly to obtain the anti-aging asphalt.
Citation Information
Patent Citations
High-storage stability rubber powder modified asphalt and preparation method thereof
CN103589176A